Dermatoglifi Pada Autisme Dan Sindrom Down di Palembang - Suciandari, Altiara Risky; Mundijo, Trisnawati; Purwoko, Mitayani (Universitas Muhammadiyah Semarang, 2018)
Dermatoglyphics on Autism and Down's Syndrome in PalembangDermatoglyphics is the study of fingerprint patterns, the number of tendrils and the number of triradius whose development is regulated by genetics. Chromosomal abnormalities that can affect the dermatoglyphic phenotype include Autism and Down's Syndrome. This study aims to determine the fingerprint pattern in patients with Autism and Down's Syndrome. This research is descriptive with a total sample of 76 patients, namely 46 patients with autism and 30 patients with Down's Syndrome who were taken by total sampling at YPAC, YBAM and Autism Clinic Anakku Palembang. From the research results, the loop pattern is the most common fingerprint pattern in Autism (57.2%) and in Down's Syndrome (80.7%). While the arch pattern is the least fingerprint pattern, namely Autism (3.7%) and Down's Syndrome (5.3%). The results of the study concluded that most people with Autism and Down's Syndrome in Palembang had a loop fingerprint pattern. Dermatoglifi adalah ilmu yang mempelajari pola sidik jari, jumlah sulur dan jumlah triradius yang perkembangannya diatur oleh genetik. Kelainan kromosom dapat mempengaruhi fenotip dermatoglifi diantaranya adalah Autisme dan Sindrom Down. Penelitian ini bertujuan untuk mengetahui pola sidik jari pada penderita Autisme dan Sindrom Down. Penelitian ini bersifat deskriptif dengan sampel penelitian berjumlah 76 penderita yaitu 46 penderita Autisme dan 30 penderita Sindrom Down yang diambil secara total sampling di YPAC, YBAM dan Klinik Autis Anakku Palembang. Dari hasil penelitian pola loop merupakan pola sidik jari terbanyak pada Autisme (57,2%) dan pada Sindrom Down (80,7%). Sedangkan pola arch merupakan pola sidik jari yang paling sedikit yaitu Autisme (3,7%) dan Sindrom Down (5,3%). Hasil penelitian disimpulkan penderita Autisme dan Sindrom Down di Palembang sebagian besar memiliki pola sidik jari loop.